Social Cohesion Metaphor in Manggarai Language (A Cultural Linguistic Analysis) - Frans Bustan; Frans Gana; Yohanis S. Sarong; Hendrikus Jehane (Universitas Nusa Cendana, 2021)
This study explores social cohesion metaphor in Manggarai language withe special reference to the forms and meanings of the linguistic phenomena used. The study is viewed from cultural linguistics with special reference to metaphor as a part of cultural conceptualization emerging in cognitive level. The study is descriptive. The result of study shows that social cohesion metaphor in Manggarai language is reflected in the forms and meanings of the linguistic phenomena used in such verbal expression as, Muku ca pu’u neka woleng curup ‘One clump of bananas doesn’t talk differently, one clump of canes doesn’t walk differently’ and (2) Nai ca anggit, tuka ca leleng ‘Hearts bound one, stomaches bound one’. The forms and meanings of the linguistic phenomena used are specific to Manggarai culture revealing conceptualization of Manggarai society on the significance of maintaining social cohesion in their contexts of living together as members of the wa’u as a patrilineal-genealogic clan